The challenge for ASEAN is to maintain a neutral relationship between the two great powers, the US and China - Bounthavong, Bouapheng; Surjaatmadja, Surachman; Anwar, Syaiful (Innovative: Journal Of Social Science Research, 2023)
The Association of Southeast Asian Nations (ASEAN) faces a significant challenge in maintaining a neutral relationship between the United States and China. As both countries compete for influence and power in the region, ASEAN must balance its relationships with both nations to prevent any potential conflicts and ensure regional stability. This task is complicated by the ongoing trade disputes and geopolitical tensions between the US and China. ASEAN must navigate these complex relationships with diplomacy and skill while continuing to promote its core values of peace, stability, and economic development. Maintaining a neutral position is essential for ASEAN to effectively address regional challenges, such as territorial disputes and the fight against terrorism. Failure to do so could lead to unintended consequences and threaten the security and prosperity of the region. As such, ASEAN's ability to maintain its neutral relationship with the US and China remains a critical challenge in the years to come.